Newbie investment simulation application / Aina Sufia Musa ... [et al.] - Musa, Aina Sufia; Mazlan, Hani Sofia; Ahmad Faisal, Fatin Hanani; An’na, Nur Syafikah; Mahmud, Nurazree (Universiti Teknologi MARA, Kedah, 2023)
This abstract contains the primary details on our app namely the Newbie Investment Simulation Application. Our goal in developing this app is to provide a hub for new investors. For instance, they could find confidence in investing through our app. Looking forward, this app will aid and welcome newcomers, from a variety of backgrounds to the investment industry. Several problems that might occur during the development of this application are finding potential users, creating an appealing interface and maintaining code quality. This is because, with the continuous updates and features to the app, the amount of data will increase. Hence, it will be challenging to maintain code quality. The main objective is to give guidance for newbies that want to experience real time trading, offer the investor more options and information based on the offered platforms and guarantee all investors who use our apps gain returns and profit. Moving on, some of our novelty includes providing users with a virtual trading portfolio which focused on shariah compliant securities, providing educational content with unlimited demonstration, sessions from expert traders and premium investment tools for fundamental and technical analysis. Some of the benefits that this app may provide are personalized experience, guidance for better practice of trading and increasing awareness upon significance of investment. Following, it's a medium of reliable source for market participants to refer to upon market information. This way, the society is closer to the investment world. Lastly, the target market entices new investors, ranging from students, adults, and senior citizens. The app also welcomes teenagers who want to draft their future financial planning early before they can start their own investment, retired individuals who want to boost their income and trainees. For starters, the advertisements will be made virtually through social media and websites.